Accelerated cellulose depolymerization catalyzed by paired metal chlorides in ionic liquid solvent - Su, Yu; Brown, Heather M.; Li, Guosheng; Zhou, Xiao-dong; Amonette, James E.; Fulton, John L.; Camaioni, Donald M.; Zhang, Z. Conrad (Applied catalysis. A, General, 2011)
The rate of cellulose hydrolysis is critically dependent on the ratio of CuCl 2/PdCl 2 in [EMIM]Cl solvent while the total catalyst loading (mol% CuCl 2 + mol% PdCl 2) is unchanged. The results of a combination of physical characterization methods for the catalytic system indicate that Cu(II) was reduced during the course of the reaction to Cu(I) only in the presence of a second metal chloride and a carbohydrate source such as cellulose in the ionic liquid system. [Display omitted] ▶ Paired metal chlorides in an ionic liquid effectively catalyzes low temperature cellulose conversion. ▶ Cellulose is depolymerized to monosaccharide under mild conditions in a single step. ▶ Copper (II) ion is reduced to Cu(I) in the presence of carbohydrates and PdCl 2 in alkylmethylimidazolium chloride ionic liquid. ▶ Ionic liquid solvent can be reused in multiple cycles for cellulose conversion. Efficient hydrolytic depolymerization of crystalline cellulose to sugars is a critical step and has been a major barrier for improved economics in the utilization of cellulosic biomass. A novel catalytic system involving CuCl 2 (primary metal chloride) paired with a second metal chloride, such as CrCl 2, PdCl 2, CrCl 3 or FeCl 3 in 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl) ionic liquid solvent has been found to substantially accelerate the rate of cellulose depolymerization under mild conditions. These paired metal chlorides are particularly active for the hydrolytic cleavage of 1,4-glucosidic bonds when compared to the rates of acid-catalyzed hydrolysis at similar temperatures (80–120 °C). In contrast, single metal chlorides with the same total molar loading showed much lower activity under similar conditions. Experimental results illustrate the dramatic effect of the second metal chloride in the paired catalytic system. An array of characterization techniques, including electron paramagnetic resonance (EPR) spectroscopy, differential scanning calorimetry (DSC), X-ray absorption fine structure (XAFS) spectroscopy, and X-ray absorption near edge structure (XANES) spectroscopy, in combination with theoretical calculations at the DFT level, was used to reveal a preliminary understanding of possible mechanisms involved in the paired CuCl 2/PdCl 2 catalytic system. We discovered that Cu(II) was reduced during the course of the reaction to Cu(I) only in the presence of a second metal chloride and a carbohydrate source such as cellulose in the ionic liquid system. Our results suggest that Cu(II) generates protons by hydrolysis of water to catalyze the depolymerization step, and serves to regenerate Pd(II) reduced to Pd(0) by side reactions. Pd(II) likely facilitates the depolymerization step by coordinating the catalytic protons, and also promotes the formation of hydroxymethylfurfural (HMF). Our results also suggest that the C2-proton of the imidazolium ring is not activated by the paired metal-chloride catalysts.